A Glimpse of Liver Resection Profile in An Indonesian Tertiary Hospital: A Retrospective Descriptive Study - Vaniara, Florencia V; Lalisang, Arnetta NL; Lalisang, Toar JM; Mazni, Yarman; Putranto, Agi S; Jeo, Wifanto S; Ibrahim, Febiansyah; Syaiful, Ridho A; Sihardo, Lam; Marbun, Vania MG (The New Ropanasuri Journal of Surgery, 2026)
Introduction. In-depth liver resection profile is needed for evaluation to improve the procedure’s outcome. This study aims to describe the clinical characteristics and outcomes of liver resection in HCC patients in Cipto Mangunkusumo Tertiary Hospital. Methods. This study retrospectively analyzed the clinical data of 19 HCC patients who underwent liver resection in Cipto Mangunkusumo Tertiary Hospital from 2021 to 2024. Demographic, clinical, laboratory, operative, and pathological data were collected. Postoperative complications were assessed using the Clavien-Dindo classification system within 30- and 90-day postoperative periods. Result. Nineteen patients were included, comprising 12 (63.2%) males and 7 (36.8%) females. Sixteen patients (84.2%) had Child-Pugh (CP) class A liver function with 10 (62.5%) CP A(5) patients and 6 (37.5%) CP A(6) patients; 3 (15.8%) patients had CP class B(7). There were 6 (31.6%) patients with thrombocytopenia and 4 (21.1%) patients with portal hypertension. Liver resection was done laparoscopically in 4 (21.1%) patients and with an open approach in 15 (78.9%) patients. Left hepatectomy was done in 3 patients (15.78%), right hepatectomy in 2 (10.5%), right anterior sectionectomy in 4 (21%), left lateral sectionectomy in 1 (5.26%), bisegmentectomy in 1 (5.26%), segmentectomy in 6 (31.58%), and non-anatomical resection in 2 (10.52%). Based on histopathologic examination, HCC was found in 13 (68.41%) patients. Among 19 patients, 12 (63.2%), 5 (26.3%), and 2 (10.5%) patients had 1 tumor, 2 tumors, and 3 tumors respectively (total tumors resected: n=28). About 16 (84.21%) patients had elevated alpha fetoprotein (AFP) (> 10 ng/mL). The mean intraoperative blood loss was 884 mL. No postoperative complications classified as Clavien-Dindo grade I-IV were observed. Two patients (10.5%) experienced postoperative mortality within 90 days (Clavien-Dindo grade V), both due to circulatory failure. Conclusion. This study presents a descriptive overview of liver resection in an Indonesian tertiary hospital. Comparative conclusions should be interpreted with caution due to the limited sample size.